THE DEVELOPMENT OF XIAOMI CARS AND ARTIFICIAL INTELLIGENCE IN THE DIGITAL ERA - Nuoyi, Xiao; Permana, Iman (President University, 2024)
In the digital age, the automotive industry is undergoing unprecedented changes, and the rapid development of artificial intelligence (AI) technology has promoted the innovation of smart cars. As a world-renowned technology company, Xiaomi has actively entered the automotive industry in recent years and is committed to integrating its advantages in smart hardware and AI into automobile manufacturing. This study aims to analyze how Xiaomi can use its technological advantages and innovation capabilities to promote the development of smart cars and explore its specific applications and achievements in the development of AI and automobiles. Using a case study method, the study found that its AI technology performs well in autonomous driving, intelligent interaction, and data analysis, improving the intelligence level of vehicles and user experience. The development of Xiaomi cars and AI has brought new development momentum to the smart car industry.